A systematic review and individual patient data meta-analysis of prognostic factors for foot ulceration in people with diabetes : the international research collaboration for the prediction of diabetic foot ulcerations (PODUS) /: the international research collaboration for the prediction of diabetic foot ulcerations (PODUS). (July 2015) - Crawford, Fay
No abstract available